Efficacy and safety of normobaric hyperoxia combined with intravenous thrombolysis on acute ischemic stroke patients. (3rd October 2021) - Li, Na; Wu, Longfei; Zhao, Wenbo; Dornbos, David; Wu, Chuanjie; Li, Weili; Wu, Di; Ding, Jianping; Ding, Yuchuan; Xie, Yunyan; Ji, Xunming
ABSTRACT: Intravenous thrombolysis elevates the prognostic level of acute ischemic stroke (AIS) patients. Normobaric hyperoxia (NBO) delays the progression of the infarct core and promotes neurological recovery. However, it is uncertain whether NBO can further raise the prognostic level of AIS patients based on intravenous thrombolysis. To explore the efficacy and safety of NBO combined with intravenous thrombolysis on AIS patients. This observational study included anterior circulation stroke patients who received intravenous thrombolysis within 4.5 h after stroke onset. These patients were divided into two groups based on whether or not they received NBO therapy. The baseline data and the prognosis of the two groups were compared. The primary outcome was the proportion of functional independence (modified Rankin Scale 0–2) at 90 days post discharge. A total of 227 patients were included in this study. 125 patients received NBO therapy combined with intravenous thrombolysis, while 102 patients received intravenous thrombolysis only. Overall, the rate of recanalization was 83.3%. Consequently, 101 patients (80.8%) who received NBO combined with intravenous thrombolysis and 63 patients (61.8%) in the control group achieved functional independence (P = 0.002). Multivariable logistic regression analysis showed that NBO combined with intravenous thrombolysis over intravenous thrombolysis alone was associated with 90-day functional independence (OR: 2.318; 95% CI: 1.226–4.381; P = 0.01). This study verified the efficacy and safety of NBO combined with intravenous thrombolysis in AIS patients. Prospective study is needed to further substantiate these findings.